Review of the types, formation mechanisms, effects, and elimination methods of binder jetting 3D-printing defects - Zhao, Kunlong; Su, Zhenhua; Ye, Zhijie; Cao, Wenxin; Pang, Jinzhuo; Wang, Xiaolei; Wang, Zhuochao; Xu, Xingchun; Zhu, Jiaqi (Journal of materials research and technology, 2023)
Additive Manufacturing (AM), commonly referred to as 3D printing, has ushered in a transformative era in the realm of material fabrication. Due to its innovative layer-adhesive methodology, Binder Jetting (BJ) is anticipated to ascend as the method of choice for synthesizing a vast array of materials. Presently, the defects inherent in BJ technique have precipitated considerable detriments to the quality of resultant components. In response, this exhaustive review delineates the foundational principles of the BJ methodology firstly and endeavors to compile a comprehensive inventory of potential defects encountered during printing. Based on formation mechanism, for the first time, the defects associated with BJ are methodically categorized into quintuple classifications, including slicing defect, powder spreading defect, single-layer printing defect, multi-layer accumulation defect and depowdering defect. Particular heed is devoted to the anomalies precipitated by the binder's interaction with the powder bed, which fundamentally sets BJ apart from conventional AM methodologies. An amalgamation of numerical algorithms and physical paradigms is introduced in each corresponding classification to arm researchers with a profound comprehension of the mechanism behind these defects. Moreover, a variety of mitigation strategies for these corresponding defects, encompassing binder selection, procedural parameter refinement, post-processual interventions and the integration of hybridized techniques are further explored and summarized. Finally, it concludes by pinpointing existing lacunae within the domain of BJ research and projects their future directions. This manuscript, by offering a comprehensive review of defects, aspires to serve as a scholarly compendium for the impending scientific and technological advancements in BJ technology.